Emerging outcome measures for nutrition trials in the critically ill. Issue 6 (November 2018) - Bear, Danielle E.; Griffith, David; Puthucheary, Zudin A.
Abstract : Purpose of review: Mortality has long been the gold-standard outcome measure for intensive care clinical trials. However, as the critical care community begins to understand and accept that survivorship is associated with functional disability and a health and socioeconomic burden, the clinical and research focus has begun to shift towards long-term physical function Recent findings: To use mortality as a primary outcome measure, one would either have to choose an improbable effect (e.g. a difference of 5–10% in mortality as a result of a single intervention) or recruit a larger number of patients, the latter being unfeasible for most critical care trials. Outcome measures will need to match interventions. As an example, amino acids, or intermittent feeding, can stimulate muscle protein synthesis, and so prevention of muscle wasting may seem an appropriate outcome measure when assessing the effectiveness of these interventions. Testing the effectiveness of these interventions requires the development of novel outcome measures that are targeted and acceptable to patients. We describe advancements in dual-energy X-ray absorptiometry scanning, bio-impedence analysis, MRI and muscle ultrasound in this patient group that are beginning to address this development need. Summary: New approaches to outcome assessment are beginning to appear in post-ICU research, which promise to improve our understanding of nutrition and exercise interventions on skeletal muscle structure, composition and function, without causing undue suffering to the patient.